How do I prove that (a/b) - (c/d) = (ad - bc)/(bd) if b =/ 0 and d =/0 Thank you
Follow Math Help Forum on Facebook and Google+
Originally Posted by papercut06 How do I prove that (a/b) - (c/d) = (ad - bc)/(bd) if b =/ 0 and d =/0 Thank you you can literally combine the two fractions on the left and you will get the ones on the right. there are dozens of ways to do this, use your favorite method of subtracting fractions.
Originally Posted by papercut06 How do I prove that (a/b) - (c/d) = (ad - bc)/(bd) if b =/ 0 and d =/0 Thank you If are elements of a field then, be definition. Then, Similarly, . Hence,
View Tag Cloud